Eradication of hepatitis C virus could improve immunological status and pyoderma gangrenosum‐like lesions. Issue 2 (3rd April 2013) - Kondo, Yasuteru; Iwata, Tomoaki; Haga, Takahiro; Kimura, Osamu; Ninomiya, Masashi; Kakazu, Eiji; Kogure, Takayuki; Morosawa, Tatsuki; Aiba, Setsuya; Shimosegawa, Tooru
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) can affect immune cells and induce various kinds of immune‐related diseases including pyoderma gangrenosum. We experienced a difficult‐to‐treat case of pyoderma gangrenosum‐like lesions in a patient with HCV infection. The patient was treated with pegylated interferon (PEG IFN)‐α‐2b and ribavirin (RBV) therapy and achieved a sustained virological response. Before the eradication of HCV, the frequency of T‐helper 17 cells was remarkably high in comparison to chronic hepatitis C patients without extrahepatic immune‐related diseases. Moreover, we could detect negative and positive strand‐specific HCV RNA in the CD19+ B lymphocytes and CD4+ T lymphocytes. However, after the eradication of HCV, the immunological status became normal and the pyoderma gangrenosum‐like lesions became stable without immunosuppressive therapy. Here, we report a sequential immunological analysis during PEG IFN/RBV therapy and the beneficial effect of HCV eradication in difficult‐to‐treat pyoderma gangrenosum‐like lesions.